2008
DOI: 10.1126/science.1153966
|View full text |Cite
|
Sign up to set email alerts
|

The Sensitivity of Polar Ozone Depletion to Proposed Geoengineering Schemes

Abstract: The large burden of sulfate aerosols injected into the stratosphere by the eruption of Mount Pinatubo in 1991 cooled Earth and enhanced the destruction of polar ozone in the subsequent few years. The continuous injection of sulfur into the stratosphere has been suggested as a "geoengineering" scheme to counteract global warming. We use an empirical relationship between ozone depletion and chlorine activation to estimate how this approach might influence polar ozone. An injection of sulfur large enough to compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
246
2
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 260 publications
(260 citation statements)
references
References 14 publications
11
246
2
1
Order By: Relevance
“…The described reduction in meridional transport of sulfate may also be true for ozone and the stratospheric ozone concentration could be reduced in the extratropics. This reduction would add to the proposed reduction of ozone due to chemical reactions (Tilmes et al, 2008). Pitari et al (2016) discuss the impact of volcanic aerosol on stratospheric dynamical processes and calculate a reduction of approximately 10 % of the extratropical mass flux of NO 2 and CH 4 after the eruption of Mt.…”
Section: Discussionmentioning
confidence: 99%
“…The described reduction in meridional transport of sulfate may also be true for ozone and the stratospheric ozone concentration could be reduced in the extratropics. This reduction would add to the proposed reduction of ozone due to chemical reactions (Tilmes et al, 2008). Pitari et al (2016) discuss the impact of volcanic aerosol on stratospheric dynamical processes and calculate a reduction of approximately 10 % of the extratropical mass flux of NO 2 and CH 4 after the eruption of Mt.…”
Section: Discussionmentioning
confidence: 99%
“…Both mechanisms have been the focus of many recent studies [Rasch et al, 2008;Wang et al, 2011], and several complications have been identified. Examples are changes to the local and regional hydrological cycles [Ricke et al, 2010], as well as stratospheric ozone depletion in the case of stratospheric sulphur injection [Tilmes et al, 2008]. Here we address a climate engineering mechanism that has so far not been tested: the perturbation of cirrus clouds to reduce their lifetime and optical thickness, thereby cooling Earth's climate.…”
Section: Introductionmentioning
confidence: 99%
“…Some commentators have suggested replacing the declining blanket of cooling sulphate aerosols in the Arctic troposphere with a deliberate injection of sulphate (or other cooling aerosol) into the Arctic stratosphere (Caldeira and Wood 2008). The amount of sulphate required would be much less (as the aerosol has a much longer lifetime in the stratosphere), but the side-effects include ozone depletion (Tilmes et al 2008). Also, returning annual mean Arctic temperatures towards e.g.…”
Section: Discussion: Risks and Responsesmentioning
confidence: 99%